Empowering Future Educators through Team-Based Projects: A Pathway to SDG 4 in Teaching Material Development - Dios Sarkity; Yudi Pratama (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2025)
Teaching materials are a cornerstone of effective learning, yet many educators struggle with designing resources that truly meet classroom needs. This study investigates the capabilities of prospective biology teachers in developing teaching materials that are responsive to real educational challenges and student needs, facilitated through team-based project learning in the Teaching Material Development course. Using a descriptive-analytical method, the research analyzed student-created materials and accompanying reports. Results revealed that 44.44% of participants successfully produced printed materials, while 55.55% developed digital resources aligned with contextual problems. Although students generally demonstrated technical proficiency in formatting their products, many fell short in addressing pedagogical relevance and learner-centered design. These findings highlight a critical need to enhance teacher education by emphasizing the development of teaching materials that are not only visually appealing but also pedagogically sound and contextually grounded. To support the goals of Sustainable Development Goal 4 (SDG 4), teacher training programs must prioritize equipping future educators with the skills to create impactful, inclusive, and needs-based learning resources.